Genetic diversity of eight maize (Zea mays) cultivars from East Nusa Tenggara (Indonesia) based on inter simple sequence repeat markers - AHMAD YANI; ABDUL RAZAQ CHASANI; BUDI SETIADI DARYONO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yani A, Chasani AR, Daryono BS. 2022. Genetic diversity of eight maize Zea mays L. cultivars from East Nusa Tenggara based on inter simple sequence repeat markers. Biodiversitas 23: 4124-4130. East Nusa Tenggara (NTT) is one of Indonesia's island that has many local maize cultivars. However, the existence of this local corn is threatened by the presence of high-yielding maize seeds. Therefore, characterization of local maize cultivars using molecular marker is needed to conserve the germplasm. This study aims to determine the genetic diversity of local maize cultivars (Zea maysL.) from  East Nusa Tenggara based on ISSR markers. This research used eight local maize cultivars (Watar Ohaq, Watar Puluq, Wata Bura, Wata Kuma, Wata Bunga, Pena Muti, Boti Pulut, and Latun Wara). Young leaves of maize were used for DNA isolation. Total genomic DNA was isolated using Genomic DNA Mini Kit for Plant (Geneaid). DNA was then amplified using 5 ISSR molecular markers (ISSR-807, ISSR-808, UBC-809, UBC-811, UBC-834). DNA band profiles were scored based on the presence or absence of bands. Genetic variability was analyzed based on the UPGMA method using the MVSP ver application. 3.1. Local maize from NTT has high genetic diversity (similarity index between 0.29-0.65). Local maize cultivars were separated into two main clusters at a similarity index of 0.43 and the grouping pattern was not influenced by the geographic location of local maize origin.